Improving Shuttlecock Product and Brand Management for Shuttlecock Entrepreneurs and Craftsmen in Nglaban Village and Sumengko, Nganjuk Regency - Triardhana, Yanuar (Journal of Sport Moovera (JSM), 2023)
Community service activities regarding shuttlecock products and brand management for shuttlecock entrepreneurs and craftspeople in Nganjuk Regency have the aim of providing more in-depth information about shuttlecock products and brands in order to improve marketing and also to advance the economy of the surrounding community. The method used is offline socialization regarding product management and shuttlecock brands using PowerPoint tools and learning modules. The community service team uses projectors, laptops, mics, outreach materials, and documentation tools as tools and materials. The socialization material contains an explanation of the quality, materials, and technology used. Not only that, but an explanation was also given regarding how to manage patents and brands when labeling products. The output of this activity is that entrepreneurs and shuttlecock craftspeople are better able to market their own products, which already have brands and patents. Apart from that, this activity is also beneficial for the surrounding community by improving the economy.